2017
DOI: 10.1002/jcb.25949
|View full text |Cite
|
Sign up to set email alerts
|

Higher Order Oligomerization of the Licensing ORC4 Protein Is Required for Polar Body Extrusion in Murine Meiosis

Abstract: We have previously shown that the DNA replication licensing factor ORC4 forms a cage around the chromosomes that are extruded in both polar bodies during murine oogenesis, but not around the chromosomes that are retained in the oocyte or around the sperm chromatin. We termed this structure the ORC4 cage. Here, we tested whether the formation of the ORC4 cage is necessary for polar body extrusion (PBE). We first experimentally forced oocytes to extrude sperm chromatin as a pseudo-polar body and found that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Insults to recombination and segregation can severely compromise reproductive outcomes ( Herbert et al ., 2015 ). Increasingly, it has become apparent that factors involved in replication during cell proliferation can also regulate important aspects of the meiotic program ( Mastro and Forsburg, 2014 ; Murakami and Keeney, 2014 ; Wu and Nurse, 2014 ; Nguyen et al ., 2017 ). In this work, we observed that the FPC components are required for proper cohesion dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Insults to recombination and segregation can severely compromise reproductive outcomes ( Herbert et al ., 2015 ). Increasingly, it has become apparent that factors involved in replication during cell proliferation can also regulate important aspects of the meiotic program ( Mastro and Forsburg, 2014 ; Murakami and Keeney, 2014 ; Wu and Nurse, 2014 ; Nguyen et al ., 2017 ). In this work, we observed that the FPC components are required for proper cohesion dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we feel compelled to make every effort to rigorously test it. Interestingly, prevention of higher order self-association of the ORC4 complex did not prevent DNA replication suggesting it did not disrupt ORC4 DNA licensing [14]. This demonstrates that the two functions ascribed to ORC4 within embryos are not mutually exclusive and, thus, likely involve interactions within different regions of the protein.…”
Section: Introductionmentioning
confidence: 93%
“…The essential regions required for higher order self-association of ORC4 for cage formation were identified at the N-terminus and within the middle domain (figure 1; [14]). The EGFP and FlAsH mORC4 were constructed using the Gibson method (Cat No.…”
Section: Generating Morc4-egfp and Morc4-flash Constructsmentioning
confidence: 99%
See 2 more Smart Citations